1997
DOI: 10.1002/adma.19970091311
|View full text |Cite
|
Sign up to set email alerts
|

Solution‐phase synthesis of luminescent materials libraries

Abstract: Communications ADVANCED 2,5-DMNPAA (Table 1, Fig. 1b). However, the "improvement factor" varies with temperature due to the fact that the Tgs of the two composites are different (17 "C and 3 "C, respectively; Table 1). For a better comparison, we used the reduced temperature TR = T -Tg as a reference. In doing so, the improvement factor is constant at about 11-12, demonstrating the significant progress achieved here.A study of the temperature dependence of the shelf lifetime performed on the eutectic mixture a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
79
0
4

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(84 citation statements)
references
References 17 publications
1
79
0
4
Order By: Relevance
“…A variety of other techniques have been implemented for synthesizing libraries of luminescent materials, including cosputtered CCS 181,182 and a solution-based technique using a multihead scanning ink-jet delivery system, 175 Fig. 46.…”
Section: -23mentioning
confidence: 99%
“…A variety of other techniques have been implemented for synthesizing libraries of luminescent materials, including cosputtered CCS 181,182 and a solution-based technique using a multihead scanning ink-jet delivery system, 175 Fig. 46.…”
Section: -23mentioning
confidence: 99%
“…In our laboratory, we also demonstrated that a multihead inkject delivery system could be used to perform automated microsynthesis of solid-state materials libraries. 15 However, for most electronic materials used in the high-tech/information industries, "thin film synthesis"-a technique with its roots in the microelectronics industry-has many advantages. A thin-film approach, "composition spread technique," has been used in the past to generate a composition-spread using off-axis codeposition.…”
Section: Synthesis Methodsmentioning
confidence: 99%
“…At present two primary methods exist for the preparation of solid-state libraries: 1) synthesis based on thin film deposition [3±6] and 2) synthesis using solution-based technologies. [7,8] These methods were then used for the discovery of superconducting, [3] magnetoresistive, [4] and luminescent [5±7, 9] materials, and electrochemical catalysts. [8] The discovery of heterogeneous catalysts is a great challenge because unlike superconductivity, magnetoresistivity, and electrochemical reactions, which can be tested by contact probes, or non-specific luminescence/fluorescence, the screening of heterogeneous catalysts requires the unambiguous detection of a specific molecule (i.e., a product) in the vicinity of small catalyst sites.…”
mentioning
confidence: 99%
“…Soc. 1980 [7] The starting materials were synthesized following the route described in reference [5a]. The alkyne group was introduced by a Sonogashira coupling reaction betweeen an aryl iodide and the corresponding alkyne.…”
mentioning
confidence: 99%